The trajectory of the ability to innovate and the financial performance of the Brazilian industry - Santos, David Ferreira Lopes [UNESP]; Basso, Leonardo Fernando Cruz; Kimura, Herbert (Elsevier, 2018)
This research analyzes the cumulative trajectory of Brazilian industry's ability to innovate and the impact of this resource on firms' financial performance. From a broad base of data taken at the firm level, a cross-sectional analysis and a longitudinal analysis were combined, through structural equation modelling, in the construction of the trajectory of resource innovation with the combined use of the following techniques: a multilevel model, latent trajectory analysis, and an autoregressive model. The empirical model shows that the ability to innovate consists of factors that are associated with internal, external, and human resources. The influence on financial performance is positive and significant when the analysis involves the long term. The autoregressive effect of the ability to innovate in time is not significant, suggesting that the innovation process is cumulative, interactive, and nonlinear. These results are relevant to emerging countries that require continued public policies and a greater intensity of business investment in the innovation process, aiming at the longevity of companies.
Keywords: Business competitiveness; Emerging markets; Innovative capacity; Profitability; Technological strategies